Optimization of dissolved oil separation by integrated mechanical and chemical treatment method - Khor, E.; Samyudia, Yudi (Institute of Electrical and Electronics Engineers Inc., 2014)
In this study, cross-flow membrane filtration was used to separate the dissolved and dispersed oil in the produced water. The purpose of this separation was to determine accurately the content of dispersed oil for pre-disposal monitoring purposes for oil and gas industry. Unavoidably, dissolved oil would not be 100 percent separated from the dispersed oil. Therefore, two objective functions for optimization were to maximize the dispersed oil in the retentate and maximize the dissolved oil in the permeate. However, in the process of filtering, some of the dissolved oil would be left on the membrane causing inaccuracy in measurement. To overcome this, chemical pre-treatment and cleaning through integrated mechanical approach were conducted to achieve the objective under the operating constraints such as transmembrane pressure (TMP). Response Surface Methodology (RSM) d-optimal technique was used and analyzed by Design-Expert v.7 software to obtain the optimum value. The operating parameter and optimum values to achieve optimum dissolved and dispersed oil separations were obtained and confirmation runs were conducted through experiment.